The Influence of Emotional Intelligence, Learning Independence, and Learning Motivation on Science Learning Outcomes of Junior High School Students in State Schools - Alifya Suci Poetry Naf'an; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Postgraduate, University of Mataram, 2026)
This study examined the direct and indirect effects of emotional intelligence and independent learning on science learning outcomes through learning motivation among public junior high school students in Kendari. The study employed a quantitative ex post facto design. The population consisted of all public junior high school students in Kendari City during the 2025/2026 academic year. A sample of 194 eighth-grade students from six public junior high schools was selected using proportional random sampling. Data were collected through Likert-scale questionnaires measuring emotional intelligence, independent learning, and learning motivation, while science learning outcomes were obtained from end-of-semester summative assessment scores. Data were analyzed using descriptive statistics and path analysis. The descriptive findings showed that students’ emotional intelligence, independent learning, and learning motivation were generally at a moderate level, whereas science learning outcomes were categorized as high. Path analysis revealed that emotional intelligence did not significantly affect learning motivation (p = 0.113). In contrast, independent learning had a significant positive effect on learning motivation (β = 0.766). Regarding science learning outcomes, neither emotional intelligence (β = −0.027) nor independent learning (β = 0.129) showed significant direct effects. However, learning motivation significantly influenced science learning outcomes (β = 0.352). The indirect effect of emotional intelligence on learning outcomes through motivation was 0.040, while the indirect effect of independent learning through motivation was 0.270. These results indicate that learning motivation plays a key mediating role in enhancing science achievement. Overall, independent learning and learning motivation contribute more substantially to students’ science learning outcomes than emotional intelligence among public junior high school students in Kendari.